(untitled) (Pedagogy of Higher and Secondary Education, 2022)
On the basis of diagnostics, the training improvement problem of a future teacher of Music hes been depicted in the article, The level of preparation of fuure teachers of Music to the usage of computer technologies in their professional activity has been analyzed.